Mapping uncertainty in genomics. Issue 2 (1st February 2018) - Howard, Heidi Carmen; Iwarsson, Erik
Abstract : The relatively novel and dynamic science of genomics holds many unknowns for stakeholders, and in particular for researchers and clinicians, as well as for participants and patients. At a time when many authors predict a future in which genomic medicine will be the norm, it is particularly relevant to discuss the unknowns surrounding genetics and genomics, including the notions of risk and uncertainty. This article will present a discussion regarding the uncertainty pertaining specifically to high throughput sequencing approaches, including the topic of incidental findings. This discussion will be guided by a taxonomy of uncertainty conceptualised around three areas of uncertainty: the source of uncertainty, the issues of uncertainty and the loci of uncertainty. This taxonomy can be used as a tool by all stakeholders involved in genomics to help further understand and anticipate uncertainties in genomics. Furthermore, to better contextualize this information, and also because this contribution is born out of an international project titled 'Mind the Risk', which addresses risk information in genetics and genomics from many different disciplinary perspectives, another aim of this article is to briefly present the basic issues pertaining to the unknowns, risks, and uncertainties of genetics as well as genomics for an audience of non-geneticists. Ultimately, the mapping out of uncertainty in genomics should allow for a better characterization of the uncertainty and consequently for a better management and communication of these uncertainties to end-users (research participants and patients).